Answer:
x= -7±√14
Explanation:
Using the quadratic equation, Use the quadratic formula to find the solutions.
−
b
±
√
b
2
−
4
(
a
c
)
2
a
-
b
±
b
2
-
4
(
a
c
)
2
a
Substitute the values
a
=
1
a
=
1
,
b
=
14
b
=
14
, and
c
=
35
c
=
35
into the quadratic formula and solve for
x
x
.
−
14
±
√
14
2
−
4
⋅
(
1
⋅
35
)
2
⋅
1
-
14
±
14
2
-
4
⋅
(
1
⋅
35
)
2
⋅
1
Simplify.
Tap for more steps...
x
=
−
7
±
√
14
x
=
-
7
±
14
The result can be shown in multiple forms.
Exact Form:
x
=
−
7
±
√
14
x
=
-
7
±
14
Decimal Form:
x
=
−
3.25834261
…
,
−
10.74165738
…